Deciphering the Success of PT Pamapersada Nusantara's Acquisition of PT Agincourt Resources: A Strategic Analysis and Impact Exploration - Utoyo, Sugeng; Muhtadin, Muhammad Harist; Pratama, Rinaldi; Abdullah, Tengku Mohd Khairal Abdullah (Universitas Negeri Semarang, 2024)
The research investigates the success factors behind the acquisition process of PT Pamapersada Nusantara (PAMA) of PT Agincourt Resources (PTAR) and provides insights into how successful strategic management within various aspects can lead to successful mergers and acquisitions in the mining sector. A qualitative case study approach was employed in the study. The 11 key managerial personnel of PTAR were engaged and an interview was used to gather extensive data on the acquisition process. Thematic analysis was conducted on the collected data using NVivo software. Five key success factors were identified: strategic communication, cultural integration, leadership, complementary resources, and employee commitment. Strategic communication was essential for ensuring the company's vision and goals were aligned to minimize change resistance. The importance of addressing and accommodating differences during the post-acquisition process to ensure smooth integration was highlighted with cultural integration. The organization's sustainable leadership was crucial during the transition and for achieving long-term success. Complementary resources were critical for operational efficiency, and employee commitment was important for stability and continued performance post-acquisition. These findings provide a useful framework for companies entering the M&A process and indicate that a holistic approach encompasses clear communication, cultural homogenization, visionary leadership, resource optimization, and integrated and committed employees.